Intelligent Information Processing V 6th IFIP TC 12 International Conference, IIP 2010, Manchester, UK, October 13-16, 2010. Proceedings - Shi, Zhongzhi; Vadera, Sunil; Aamodt, Agnar; Leake, David; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2010)
This book constitutes the refereed proceedings of the 6th IFIP TC 12 International Conference on Intelligent Information Processing, IIP 2010. The 35 revised papers presented together with 4 short papers were selected from more than 50 submissions. They are organized in topical sections on semantic web services, automatic reasoning, case-based reasoning, data mining, web mining, web search, knowledge representation, natural language processing, image processing, and pattern recognition.
Keynote Presentations -- Case-Based Reasoning Tomorrow: Provenance, the Web, and Cases in the Future of Intelligent Information Processing -- Knowledge Mining Biological Network Models -- Multivariate Bandits and Their Applications -- Image Semantic Analysis and Understanding -- Semantic Web Services -- Collaboration in Agent Grid Based on Dynamic Description Logics -- Requirement Driven Service Composition: An Ontology-Based Approach -- Multi-agent and Workflow-Based Web Service Management Model -- Semantic Approach for Service Oriented Requirements Modeling -- Automatic Reasoning -- Extend Atomic Action Definitions of DDL to Support Occlusions and Conditional Post-conditions -- Preservative Translations between Logical Systems -- The Description Logic for Relational Databases -- Non-Functional Requirements Elicitation and Incorporation into Class Diagrams -- Case-Based Reasoning -- Architectures Integrating Case-Based Reasoning and Bayesian Networks for Clinical Decision Support -- Event Extraction for Legal Case Building and Reasoning -- Applications of CBR in Oil Well Drilling: A General Overview -- Data Mining -- Associated Clustering and Classification Method for Electric Power Load Forecasting -- Two Improvement Strategies for PSO -- Mining Temporal Patterns of Technical Term Usages in Bibliographical Data -- Automated Empirical Selection of Rule Induction Methods Based on Recursive Iteration of Resampling Methods -- Web Mining -- Adaptive Web-Based Instruction for Enhancing Learning Ability -- Extracting Comparative Commonsense from the Web -- Detecting Temporal Pattern and Cluster Changes in Social Networks: A Study Focusing UK Cattle Movement Database -- Unstructured P2P-Enabled Service Discovery in the Cloud Environment -- Web Search -- Using Global Statistics to Rank Retrieval Systems without Relevance Judgments -- Rule Learning with Negation: Issues Regarding Effectiveness -- Integrating Web Videos for Faceted Search Based on Duplicates, Contexts and Rules -- An Efficient Data Indexing Approach on Hadoop Using Java Persistence API -- Knowledge Representation -- Knowledge Engineering for Non-engineers -- Attribute Exploration Algorithms on Ontology Construction -- Intelligent Business Transaction Agents for Cross-Organizational Workflow Definition and Execution -- Knowledge Granularity and Representation of Knowledge: Towards Knowledge Grid -- Natural Language Processing -- Combining the Missing Link: An Incremental Topic Model of Document Content and Hyperlink -- A General Approach to Extracting Full Names and Abbreviations for Chinese Entities from the Web -- An English-Arabic Bi-directional Machine Translation Tool in the Agriculture Domain -- A Laplacian Eigenmaps Based Semantic Similarity Measure between Words -- Image Processing -- A Filter-Based Evolutionary Approach for Selecting Features in High-Dimensional Micro-array Data -- A Novel Distribution of Local Invariant Features for Classification of Scene and Object Categories -- Adult Image Detection Combining BoVW Based on Region of Interest and Color Moments -- Pattern Recognition -- Multimedia Speech Therapy Tools and Other Disability Solutions as Part of a Digital Ecosystem Framework -- Noise Estimation and Noise Removal Techniques for Speech Recognition in Adverse Environment -- Proximity User Identification Using Correlogram -- Erratum: An Efficient Data Indexing Approach on Hadoop Using Java Persistence API.
Keywords: Computer science; Database management; Data mining; Information storage and retrieval systems; Artificial intelligence; Computer vision; Optical pattern recognition; Computer Science; Information Storage and Retrieval; Artificial Intelligence (incl. Robotics).; Database Management; Data Mining and Knowledge Discovery; Pattern Recognition; Image Processing and Computer Vision